THE INFLUENCE OF COMPETENCE, COMPENSATION AND LEADERSHIP STYLE ON PERFORMANCE THROUGH JOB SATISFACTION AT THE INSPECTORATE GENERAL OF THE MINISTRY OF - Sugiono, Edi; Efendi, Suryono; Susilo, Joko (2021)
The performance of the company is strongly influenced by the performance of the company's employees. This performance can come from within the employee or outside the employee, such as competence, compensation, and leadership style. However, from several previous studies, there are differences in research results. The purpose of this research is to be able to analyze competence, compensation, and leadership style and their effect on performance through job satisfaction. The population used is all employees in the Inspectorate General of the Ministry of Agriculture. The analytical method used is quantitative using the Structural Equation Model (SEM). The results of the study show that job satisfaction can mediate the effect of competence, compensation, and leadership style on employee performance. Then job satisfaction can have a positive and significant impact on employee performance.